Analisis Kejadian Anemia Pada Ibu Hamil di Puskesmas Kampili Kabupaten Gowa - Isnaeny Isnaeny (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Anemia in pregnancy is a national problem because it reflects the socio-economic welfare values of society, and has a huge influence on the quality of human resources. The high incidence of anemia in pregnant women is very worrying because it can have a negative impact on mothers during pregnancy, childbirth and postpartum. The factors that influence the incidence of anemia are lack of nutrients, apart from that, education and maternal parity are closely related to the incidence of anemia. The aim of this study was to obtain information about anemia in pregnant women focusing on education, parity, maternal age and gestational age. This type of research is descriptive, namely to find out the general picture of the incidence of anemia in pregnant women, where the information is obtained from the results of medical records at the Kampili Community Health Center. Overall the population was 1090 and a sample of 375 pregnant women who experienced anemia were obtained. The results of the study concluded that the average education level of mothers who experienced anemia was mothers with a low education parity of more than 4, the mother's age was under 20 years and the gestational age was in the second trimester.